HEMATOLOGY OF ASIAN REDTAIL CATFISH (Hemibagrus nemurus) REARED IN MEDIA WITH REGULAR ADDITION OF PROBIOTICS - Lestari, Rona; Syawal, Henni; Lukistyowati, Iesje (Asian Journal of Aquatic Sciences, 2023)
Multi-cell probiotic containing bacteria Nitrosomonas sp., Nitrobacter sp., and Bacillus sp. This research was conducted from March to May 2021 at the Fish Disease and Parasite Laboratory, Department of Aquaculture, Faculty of Fisheries and Marine, Universitas Riau. This study aimed to analyze the hematology of Asian redtail catfish reared in media that was added with probiotics periodically and to obtain the best time interval for giving probiotics to the rearing medium. The method used in this study is an experimental method by applying a Completely Randomized Design (CRD) with five treatment levels and three replications. The treatments used were the administration of probiotics at a dose of 0,01 mL/L of water with different time intervals, P0 (without treatment), P1 (5 days once), P2 (10 days once), P3: (15 days once), and P4 (20 days once). Fish were reared for 50 days. The results show that the Asian redtail catfish reared with the addition of probiotics in the rearing medium had a significant effect (P<0.05) with the best time interval being once every 5 days in the P1 treatment, seen from the total erythrocytes 2.43 x 106 cells/mm3, hematocrit level 28.67%, hemoglobin level 7.40 g/dL, total leukocytes 9.92 x 104 cells/mm3, leukocrit level 1.83%, and glucose 49.67 g /dL. Water quality during the study was still in the normal range that could support the growth of Asian redtail Catfish, namely temperature 26-27.1 C, pH 5.8-6.5, DO 6.0-7.4 mg/L, and ammonia 0.0011-6.5 0.0047 mg/L.